2012
DOI: 10.5603/cj.2012.0108
|View full text |Cite
|
Sign up to set email alerts
|

Role of biological and non biological factors in congestive heart failure mortality: PREDICE-SCORE: A clinical prediction rule

Abstract: Background: Congestive heart failure (HF) is a chronic, frequent and disabling condition but with a modifiable course and a large potential for improving. The aim of this project was to develop a clinical prediction model of biological and non biological factors in patients with first diagnosis of HF that facilitates the risk-stratification and decision-making process at the point of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Following the title and abstract screening process, 292 studies were deemed eligible for full‐text screening. Ultimately, during the final phase of full‐text screening, 65 studies (comprising 88 cohorts) met the inclusion criteria and were included in the subsequent meta‐analysis 10–74 . One additional study was identified through a manual cross‐reference of the included studies, bringing the total to 66 studies 75 (online supplementary Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Following the title and abstract screening process, 292 studies were deemed eligible for full‐text screening. Ultimately, during the final phase of full‐text screening, 65 studies (comprising 88 cohorts) met the inclusion criteria and were included in the subsequent meta‐analysis 10–74 . One additional study was identified through a manual cross‐reference of the included studies, bringing the total to 66 studies 75 (online supplementary Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…. ) can be responsible for an acute HF decompensation [19][20][21][22][23]. These triggers affect the fluid balance regulatory mechanisms, leading to hydric overload.…”
Section: Introductionmentioning
confidence: 99%
“…Heart failure is the most common disease with high mortality and morbidity rate in the worldwide [2]. Co-morbidities are important in patients with HF.…”
mentioning
confidence: 99%